Chlorophyll hormesis: Are chlorophylls major components of stress biology in higher plants? - Agathokleous, Evgenios; Feng, ZhaoZhong; Peñuelas, Josep (The Science of the total environment, 2020)
High oxidative stress inhibits the synthesis and accumulation of chlorophylls, the pigments that absorb and use light. We collated evidence from a diverse array of studies demonstrating that chlorophyll concentration increases in response to low-level stress and decreases in response to high-level stress. These observations were from 33 species, >20 stress-inducing agents, 43 experimental setups and 177 dose responses, suggesting generality. Data meta-analysis indicated that the maximum stimulatory response did not differ significantly among species and agents. The stimulatory response maximized within a defined time window (median = 150–160% of the control response), after which it decreased but remained elevated (median = 120–130% of control response). The common stimulation of chlorophylls by low-level stress indicates that chlorophylls are major components of stress biology, with their increased concentration at low-level stress suggestive of their requirement for normal functioning and health. Increased chlorophyll concentration in response to low-level stress may equip systems with an enhanced capacity for defense against high-level (health-threatening) challenges within defined time windows, such as pollution or herbivores. These developments have wide-ranging implications in ecophysiology, biotic interactions and evolution.